1990
DOI: 10.1136/bmj.300.6724.563
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vertebral compression fractures due to osteoporosis in ankylosing spondylitis.

Abstract: Objective-To determine the prevalence of vertebral compression fractures due to osteoporosis in patients with ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
2
12

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(64 citation statements)
references
References 9 publications
2
48
2
12
Order By: Relevance
“…Bony overgrowth in AS has been considered a structural damage arising from chronic immune activation and inflammation, [3] although the link between inflammation and ankylosis is not completely understood in this disease. [3,4] A study by Ralston et al [5] emphasized the difference between the processes taking place in cortical versus trabecular bone in AS. While trabecular bone mass decreases, leading to vertebral osteoporosis, specific sites of the cortical bone start to proliferate and expand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bony overgrowth in AS has been considered a structural damage arising from chronic immune activation and inflammation, [3] although the link between inflammation and ankylosis is not completely understood in this disease. [3,4] A study by Ralston et al [5] emphasized the difference between the processes taking place in cortical versus trabecular bone in AS. While trabecular bone mass decreases, leading to vertebral osteoporosis, specific sites of the cortical bone start to proliferate and expand.…”
Section: Introductionmentioning
confidence: 99%
“…While trabecular bone mass decreases, leading to vertebral osteoporosis, specific sites of the cortical bone start to proliferate and expand. [5,3] In general, AS is associated with bone loss in the vertebrae and an increased prevalence of vertebral fractures. [6,7] Cooper et al [6] identified markedly increased relative risk of vertebral morphometric deformities in patients with AS compared with the control population.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, osteoporotic fractures are more prevalent in patients with AS than in the general population [2][3][4]. Due to the formation of paravertebral calcification false interpretation of spine bone density measured by dual-energy x-ray absorptiometry (DXA) can occur.…”
Section: Introductionmentioning
confidence: 99%
“…For example, abdominal exercises that actively flex the trunk may be problematic for individuals with lumbar disk pathologies due to increased intradiscal pressure 18 and lumbar spine compression, 3 and for individuals with osteoporosis due to the risk of vertebral compression fractures. 21 However, these same individuals may be asymptomatic during abdominal exercises that maintain a relatively neutral spine and pelvis. In contrast, individuals with facet joint syndrome, spondylolisthesis, and vertebral or intervertebral foramen stenosis may not tolerate exercises such as the Ab Slide and Torso Track due to the extended spine position.…”
mentioning
confidence: 99%